INKUBATOR PENETAS TELUR AYAM KAMPUNG OTOMATIS BERBASIS MIKROKONTROLER - Abdurrahman sani; Muhammad Fahrurrozi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2022)
Microcontroller is a functional computer system on a chip. It contains a processor core, memory, and input output equipment. Microcontroller is a computer on a chip that is used to control electronic equipment. One of the uses of a microcontroller is to embed it in a chicken incubator egg incubator. An incubator is a device that is heated by electricity at a certain temperature that is used to incubate eggs, microbes and warm babies who are born prematurely. In the incubator there is a lamp that is used to warm the eggs so that the eggs can hatch with good quality by using an incandescent lamp. Utilization of the microcontroller in the incubator is used to manage the incubator heat automatically to suit the needs of the eggs in their natural habitat. The results of this research are in the form of a prototyping of chicken egg hatching incubators for breeders. The results obtained from monitoring the use of the incubator for 2 months were that 90% of the eggs successfully hatched into chicks.